STRATEGI KOMUNIKASI ISLAM DALAM PEMBINAAN AGAMA PADA SUKU ANAK DALAM BUKIT DUO BELAS KECAMATAN PAUH KABUPATEN SAROLANGUN PROVINSI JAMBI - Mila Wahyuni (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
This study uses a field research field research with qualitative methods that describe the results of research in the form of the written word, which is the result of observation and interviews with informants researchers. The informant researchers is the coach or who provide religious guidance to the tribal children in Bukit village Aek Black Duo Belas districts Sarolangun Pauh district of Jambi province, while six people informant informant, they like Dai who served in the local village. The Chief who had already embraced Islam, as well as figures or leaders of local communities, who live in Area settlements tribal groups of children in, then a few people from ethnic groups of children in and observers tribal children in the district Sarolangun, while the means of collecting data using observation and interviews, techniques and checking the validity of the data is dekskriktif and triangulation.Based on observations obtained that, of the difficulties the seriousness of the builder provide, show or produced significant results in the group of tribal children in as evidence that the communication of Islam capable of embracing them to be able to choose Islam as a new confidence for them and leave animism which is a belief that has been long before they believe to be true, which will aim other than they receive special attention from the government, the most impressive thing in addition to bringing a better life for them, their families and descendants, of course it can presumably they coexist in harmony with the environment and local communities.